Gold nanorods assisted photothermal therapy of bladder cancer in mice: A computational study on the effects of gold nanorods distribution at the centre, periphery, and surface of bladder cancer. (March 2023) - Cheong, Jason KK; Ooi, Ean H; Chiew, Yeong S; Menichetti, Luca; Armanetti, Paolo; Franchini, Mauro Comes; Alchera, Elisa; Locatelli, Irene; Canu, Tamara; Maturi, Mirko; Popov, Viktor; Alfano, Massimo
Highlights: 3D model of mouse bladder was constructed to simulate treatment outcome of GNR-PTT. GNRs were introduced via intratumoural injection and intravesical instillation. GNR-PTT treatment outcome is affected by the GNR distribution inside the tumour. Intravesical instillation is advantageous over intratumoural injection during GNR-PTT. Abstract: Background and objectives: Gold nanorod-assisted photothermal therapy (GNR-PTT) is a cancer treatment whereby GNRs incorporated into the tumour act as photo-absorbers to elevate the thermal destruction effect. In the case of bladder, there are few possible routes to target the tumour with GNRs, namely peri /intra-tumoural injection and intravesical instillation of GNRs. These two approaches lead to different GNR distribution inside the tumour and can affect the treatment outcome. Methodology: The present study investigates the effects of heterogeneous GNR distribution in a typical setup of GNR-PTT. Three cases were considered. Case 1 considered the GNRs at the tumour centre, while Case 2 represents a hypothetical scenario where GNRs are distributed at the tumour periphery; these two cases represent intratumoural accumulation with different degree of GNR spread inside the tumour. Case 3 is achieved when GNRs target the exposed tumoural surface that is invading the bladder wall, when they are delivered by intravesical instillation. Results: Results indicate that for a laser power of 0.6 W and GNR volume fraction of 0.01%, Case 2 and 3 were successful in achieving complete tumour eradication after 330 and 470 s of laser irradiation, respectively. Case 1 failed to form complete tumour damage when the GNRs are concentrated at the tumour centre but managed to produce complete tumour damage if the spread of GNRs is wider. Results from Case 2 also demonstrated a different heating profile from Case 1, suggesting that thermal ablation during GNR-PTT is dependant on the GNRs distribution inside the tumour. Case 3 shows similar results to Case 2 whereby gradual but uniform heating is observed. Cases 2 and 3 show that uniformly heating the tumour can reduce damage to the surrounding tissues. Conclusions: Different GNR distribution associated with the different methods of introducing GNRs to the bladder during GNR-PTT affect the treatment outcome of bladder cancer in mice. Insufficient spreading during intratumoural injection of GNRs can render the treatment ineffective, while administered via intravesical instillation. GNR distribution achieved through intravesical instillation present some advantages over intratumoural injection and is worthy of further exploration.